The Korean path? Corporate social responsibility and Korean transnational corporations in South Africa - Jeong, Da Un (My University, 2016)
This research is a conceptual inquiry into the orientation and practice of corporate social responsibility (CSR) of Korean transnational corporations (TNCs) in South Africa. Through a case study of Mana Technologies’ CSR programme, the research aims to explore Korean TNCs’ conceptualisation of CSR and their rationale behind the engagement in CSR initiatives. The research found that Korean corporations in South Africa draw on the ‘business case’ for CSR in their conceptualisation of CSR. Therefore, CSR orientation, policies and practice of Korean TNCs, to some extent, align with those of TNCs globally. Notwithstanding some similarities with global CSR practices, a Korean path to CSR seems to exist in South Africa. While the Korean CSR programmes in South Africa are underpinned by rational motivation, they institutionalise individuals with seemingly caring and genuine heart in the implementation of their CSR programmes. Thus, CSR effectively becomes a mechanism to shift the image of Korean corporations from greedy representatives of global capital to a caring corporate citizen genuinely committed to the development of society.
Thesis (M.A. (Development Studies))--University of the Witwatersrand, Faculty of Humanities, School of Social Sciences, 2016
Keywords: Corporate social responsibility--South Africa; International business enterprises--South Africa; Social responsibility of business--South Africa; International business enterprises--South Africa